Behavior, Change, and Self-Leadership with Wearable Activity Trackers: A Case Study of Ultra Endurance Athletes - Rauma, Ella (2024)
Wearable Activity Trackers are built to influence and create change in human behavior. While the actual effectiveness is still a matter of debate, most research has focused on focus groups from a health perspective or individuals with the need to decrease sedentary behavior. This study aims on defining how wearable activity trackers influence the activity and recovery behavior of ultra endurance athletes. The research is a qualitative case study and the data collection method is semi-structured thematic interview. Five ultra endurance athletes highly engaged to wearable activity tracker usage were interviewed. The results suggest that wearable activity trackers do influence the activity and recovery behavior and change initiatives of ultra endurance athletes. The athletes were engaged with the actual metrics rather than the behavior change techniques, yet the trust grew gradually through evidence. They expressed major self-leadership and self-efficacy. Compliance with the wearable was visible when the subjective feeling matched. In other words, the behavior was self, not IT-lead and the individuals were able to transform wearable-driven behavior to self driven, turning external motivation to internal. Arguably, while wearables can support and reinforce change, they are unlikely to be the sole drivers of lasting behavioral modifications. Sustainable behavioral change with wearable activity trackers is a complex combination of self- and wearable-driven techniques and external enablers.